Positive Association Between Helicobacter pylori Infection and Metabolic Syndrome in a Korean Population: A Multicenter Nationwide Study - Lim, Seon Hee; Kim, Nayoung; Kwon, Jin Won; Kim, Sung Eun; Baik, Gwang Ho; Lee, Ju Yup; Park, Kyung Sik; Shin, Jeong Eun; Song, Hyun Joo; Myung, Dae-Seong; Choi, Suck Chei; Kim, Hyun Jin; et al. (Digestive diseases and sciences, 2019)
Background and Aim Helicobacter pylori ( H. pylori ) infection causes extra-gastrointestinal as well as gastric diseases. This analytical cross-sectional study was performed to investigate the association between H. pylori infection and metabolic syndrome in a Korean population. Methods Anthropometric and metabolic data, as well as anti- H. pylori IgG antibodies, were measured in 21,106 subjects who participated in a health checkup between January 2016 and June 2017. The classification of metabolic syndrome followed the revised National Cholesterol Education Program criteria. Results After excluding subjects with a history of H. pylori eradication therapy, or gastric symptoms, the seropositivity of H. pylori was 43.2% in 15,195 subjects. H. pylori -positive participants had significantly higher body mass index (BMI), waist circumference, total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and lower high-density lipoprotein (HDL-C) than did seronegative participants ( P < 0.05). After adjusting for confounders, high TC, low HDL-C, and high LDL-C were associated with H. pylori seropositivity. Finally, the prevalence of metabolic syndrome was higher in H. pylori -seropositive subjects than in negative ones (27.2% vs. 21.0%, P < 0.05), and H. pylori seropositivity increased the likelihood of metabolic syndrome (OR 1.19, 95% CI 1.09–1.31, P < 0.001) after adjusting for sex, age, BMI, smoking, residence, household income, and education level. However, the association between H. pylori seropositivity and metabolic syndrome disappeared in those ≥ 65 years old. Conclusions H. pylori infection plays an independent role in the pathogenesis of metabolic syndrome in Koreans under 65 years old.